Radioprotective Potency of Nanoceria - Alvandi, Maryam; Shaghaghi, Zahra; Farzipour, Soghra; Marzhoseyni, Zeynab (Current Radiopharmaceuticals, 2024)
Cancer presents a significant medical challenge that requires effective management. Current cancer treatment options, such as chemotherapy, targeted therapy, radiotherapy, and immunotherapy, have limitations in terms of their efficacy and the potential harm they can cause to normal tissues. In response, researchers have been focusing on developing adjuvants that can enhance tumor responses while minimizing damage to healthy tissues. Among the promising options, nanoceria (NC), a type of nanoparticle composed of cerium oxide, has garnered attention for its potential to improve various cancer treatment regimens. Nanoceria has demonstrated its ability to exhibit toxicity towards cancer cells, inhibit invasion, and sensitize cancer cells to both radiation therapy and chemotherapy. The remarkable aspect is that nanoceria show minimal toxicity to normal tissues while protecting against various forms of reactive oxygen species generation. Its capability to enhance the sensitivity of cancer cells to chemotherapy and radiotherapy has also been observed. This paper thoroughly reviews the current literature on nanoceria's applications within different cancer treatment modalities, with a specific focus on radiotherapy. The emphasis is on nanoceria's unique role in enhancing tumor radiosensitization and safeguarding normal tissues from radiation damage.
Keywords: radiotherapy